1998
DOI: 10.1073/pnas.95.24.14184
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking the functions of the chromaffin cell α 7 nicotinic receptor by using short pulses of acetylcholine and selective blockers

Abstract: Methyllycaconitine (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 42 publications
1
99
1
Order By: Relevance
“…5B). Nevertheless, because the only concentration of ACh used to build these curves (100 M) matches with the EC 50 values of ACh acting on ␣ 3 ␤ 4 and ␣ 7 nAChRs (98 and 95 M, respectively), and similar IC 50 values for catestatin blockade on both receptor types were found, it is possible to conclude that the two main classes of nAChRs controlling the catecholamine release at the splanchnic-chromaffin cell synapse (López et al, 1998) are potential targets for catestatin. Moreover, the fact that the rest of the nAChR subtypes tested do not differ significantly in their sensitivity to the peptide suggests that catestatin might be a ubiquitous regulator of the cholinergic neurotransmission in other areas in addition to the adrenal medulla, i.e., the brain, where ␣ 4 and ␤ 2 nAChR subunits predominate (Gopalakrishnan et al, 1996), or sympathetic ganglia that express ␣ 3, ␤ 2 , ␣ 7 , and ␤ 4 nAChR subunits (Yu and Role, 1998;Xu et al, 1999) and where endogenously formed catestatin has been documented (Taylor et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5B). Nevertheless, because the only concentration of ACh used to build these curves (100 M) matches with the EC 50 values of ACh acting on ␣ 3 ␤ 4 and ␣ 7 nAChRs (98 and 95 M, respectively), and similar IC 50 values for catestatin blockade on both receptor types were found, it is possible to conclude that the two main classes of nAChRs controlling the catecholamine release at the splanchnic-chromaffin cell synapse (López et al, 1998) are potential targets for catestatin. Moreover, the fact that the rest of the nAChR subtypes tested do not differ significantly in their sensitivity to the peptide suggests that catestatin might be a ubiquitous regulator of the cholinergic neurotransmission in other areas in addition to the adrenal medulla, i.e., the brain, where ␣ 4 and ␤ 2 nAChR subunits predominate (Gopalakrishnan et al, 1996), or sympathetic ganglia that express ␣ 3, ␤ 2 , ␣ 7 , and ␤ 4 nAChR subunits (Yu and Role, 1998;Xu et al, 1999) and where endogenously formed catestatin has been documented (Taylor et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that nAChRs containing ␣ 3 and ␤ 4 subunits are dominant in the control of catecholamine secretion from these cells (Wilson and Kirshner 1977;Kumakura et al, 1980;Trifaró and Lee, 1980;Kilpatrick et al, 1981). However, bovine chromaffin cells additionally express ␣ 7 nAChRs (García-Guzman et al, 1995), which are also functional (López et al, 1998). Therefore, it was of interest to know whether catestatin blocked nAChR subunit combinations other than the ␣ 3 ␤ 4 .…”
Section: Effects Of Catestatin On Nachrs Composed Of Different Subunimentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple ␣ and ␤ subunits have been identified in rat chromaffin cells (Di Angelantonio et al, 2003;Sala et al, 2008). Although the ␣3 subunit constitutes a major component of nAChRs activated in response to synaptically released acetylcholine (Criado et al, 1992;Nooney and Feltz, 1995;Barbara and Takeda, 1996), ␣7-built receptors are also involved in acetylcholine-mediated responses (Ló pez et al, 1998;Martin et al, 2003Martin et al, , 2005. The expression of ␣9 and ␣10 subunits in rat chromaffin cells (L. A. Olivos-Oré, L. Solís, C. Montiel, and A. R. Artalejo, unpublished observations) extends the tissular distribution of ␣9/␣10 nAChRs to a neuroendocrine tissue and raises the question of their role.…”
Section: Introductionmentioning
confidence: 99%